Review of Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper ;, 2006)
Immediately following the effectiveness of the decisions on the Multilateral Debt Relief Initiative (MDRI) and the Exogenous Shocks Facility (ESF), debt relief totaling SDR 2.3 billion was delivered to 19 qualifying members, including 17 countries under the enhanced Heavily Indebted Poor Countries (HIPC) Initiative and two non-HIPCs, on January 6, 2006, with financing from the HIPC Umbrella sub-accounts and the newly established MDRI Trusts.